Trade unions and the provision of social protection in South Africa : a case study on the influence of CONSAWU and COSATU on pension policies in post apartheid era. - Shaba, Wezi Galera (My University, 2012)
The post apartheid South African government inherited a racially designed social protection system. This system was discriminatory, mainly served the white population and excluded the majority of black South Africans. Recognising this discrepancy, the ANC government embarked on the transformation of the existing social welfare programs which aimed at ensuring that basic welfare rights are provided to all citizens, priotising those who had historically been disadvantaged. Many years have passed since the democratic government came to power and started to carry out reforms that were aimed at increasing coverage of both occupational and social pensions. While great slides have been made in extending coverage of social pensions, ironically, only slightly more than half (52%) of South Africa’s 12.6 million workers are covered. This study aimed at investigating the extent to which trade unions have been able to influence policy formulation related to social protection, especially those aimed at increasing coverage of social and occupational pensions. The study focused on the roles played by CONSAWU and COSATU and it used in-depth interviews as the main tool for collecting data. Interviewees were identified using purposive sampling from both trade unions and government departments that closely deal with social protection issues. The study has revealed that trade unions’ influence in policy formulation for social protection has not been effective enough. This could be attributed in part to the paternalistic approach by government departments towards labour in policy issues and inadequate vigilance from trade unions to claim their rightful position.
Keywords: Trade unions; Pension policies; Post-apartheid South Africa